Impact Of Information Communication Technology On Customer Satisfaction In Airline Industry - Sankaran, Muthulakshmi (2003)
This project deals in the main, with the problem of customer satisfaction in a service industry , namely, the Airline Industry, with special reference to the Passenger Community. The factor that is taken up for special investigation is the effect of impact of Information Communication Technology.